Review: Oman in Early Islamic History - Smith, G. Rex (Journal of Semitic studies, 2004)
Oman in Early Islamic History Isam Al-Rawas , Ithaca Press, Reading 2000. xi + 232. Price: £35.00 . ISBN: 0-86372-238-5